Digitalisasi Pelayanan E-KTP di Dinas Kependudukan dan Pencatatan Sipil Kabupaten Bone Bolango - Huntua, Fadilla S.; Tohopi, Rustam; Tantu, Romy (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
This research aimed to elucidate the implementation of digitalization of e- KTP (Electronic IDs) services at the Population and Civil Registration Agency (Disdukcapil) of Bone Bolango Regency with four indicators: system, service, information, and feedback. The research object was the Disdukcapil of Bone Bolango Regency. This research employed the qualitative descriptive method, collecting the data through observation, interviews, and documentation with qualitative data analysis.The research findings denoted that (1) The e-KTP service system, implemented via the SI DIA application, follows a structured process involving input, processing, and output data from applicants. These applicants must possess a KTP and complete registration in the national population database through the online system. The availability of information from the e-KTP service through the SI DIA has also been carried out well by the Bone Bolango Regency Disdukcapil, namely by providing information to the public through an outreach program. (2) Information about processes and procedures was provided clearly and easily understood by the public, and it was observable from the many people who have made e-KTPs through the SI DIA. (3) The service form of the e-KTP service through the SI DIA was demonstrated by employees, particularly the Bone Bolango Regency Disdukcapil office, which has provided good service. In this case, employees were responsive in serving, friendly, polite in their speech, and responsive to criticism and suggestions from the public. (4) The form of feedback from implementing e-KTP services through the SI DIA has been followed up by employees based on suitability, effectiveness, timeliness and procedures.